The Influence of Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, and Learning Motivation on the Level Of Accounting Comprehension (A Study on Accounting Students at State Universities in Pekanbaru City) - Nasty, Fitri Amanda; Novius, Andri; Djamil, Nasrullah (InJEBA : International Journal of Economics, Business and Accounting, 2024)
This research is a quantitative study which aims to determine the influence of intellectual intelligence, emotional intelligence, spiritual intelligence, learning motivation on the level of understanding of accounting among state university accounting students in the city of Pekanbaru. The total sample for this research was 100 active undergraduate students majoring in Accounting. This research uses primary data obtained through distributing questionnaires. Data analysis uses multiple linear regression which consists of descriptive statistical analysis, classical assumption testing, and hypothesis testing. The results of multiple linear regression analysis show that partially the variables intellectual intelligence, emotional intelligence, intellectual intelligence and learning motivation have a positive effect on the level of understanding of accounting. Simultaneously intellectual intelligence, emotional intelligence, spiritual intelligence, learning motivation have a significant effect on the level of understanding of accounting.